Nanofiber wound dressing with photo-thermal chemical synergistic antibacterial effect and preparation method
The nanofiber dressing prepared by electrospinning combines photothermal and chemical synergistic antibacterial effects to solve the problems of poor anti-infection ability of wound dressing and drug stimulation, achieving an efficient antibacterial and safe wound healing environment for bacteria.
Patent Information
- Application Number
- CN202411258934.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-31
AI Technical Summary
Existing wound dressings have poor anti-infection ability, and drug-loaded dressings may lead to bacterial resistance and drug response to skin irritation.
Nanofiber dressing prepared by electrospinning method, graphene oxide modified branched polyethyleneimine (GO-BPEI) is added as photothermal antibacterial component and lanthanum chloride as chemical antibacterial component to form PVA/CS/GO-BPEI /La nanofiber dressing, combining photothermal and chemical synergistic antibacterial effects.
It achieves a broad-spectrum, efficient and selective antibacterial effect on bacteria, avoids drug resistance and skin irritation risks, and improves mechanical properties, breathability and water absorption, and is suitable as a wound dressing.
Smart Images

Figure CN119215214A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of medical dressings for repairing skin injury wounds, and specifically relates to a nanofiber wound dressing with photothermal and chemical synergistic antibacterial effects and a preparation method thereof. The nanofiber dressing is prepared by an electrospinning method. Background Art
[0002] As a human organ that directly interacts with the external environment, the skin is susceptible to external physical, chemical and infectious microbial influences, which can cause skin damage. Skin dressings play a key role in protecting wounds from pathogen invasion. However, traditional wound dressings can only provide minimal wound protection and have many disadvantages, including inability to keep wounds moist, poor air permeability and susceptibility to infection.
[0003] Electrospinning is a simple and cost-effective preparation method that has been widely used to produce nanofiber dressings with high specific surface area and porosity. Its high porosity and specific surface area provide favorable conditions for absorbing wound exudate and improving permeability, while its three-dimensional structure can serve as a barrier to bacterial invasion. Electrospun nanofibers have been widely used in skin wound dressings because their structure and biological functions are similar to those of the extracellular matrix. However, there are still many challenges in using electrospun dressings to promote skin wound healing, such as wound inflammation, angiogenesis, and bacterial infection. Therefore, it is an urgent clinical need to develop an electrospun dressing that can have a positive effect in certain aspects, such as inhibiting bacterial infection.
[0004] Some dressings have antibacterial properties by adding antibiotics, such as gentamicin, but they are easy to make bacteria resistant (CN202110912992.5). At the same time, some quinolones are antibacterial agents, and direct contact with the skin may cause local irritation or allergic reactions (CN110152049B). Photothermal inhibition is a new antibacterial method that is different from chemical inhibition. It refers to killing bacteria by converting light energy into heat energy. It has the advantages of non-invasiveness, high efficiency, broad spectrum, and good selectivity. It is a potential antibacterial method. At the same time, compared with drug-loaded antibacterial, photothermal inhibition has the following main advantages: (1) It has a wide range of antibacterial properties and is also effective against drug-resistant bacteria; (2) There is no risk of side effects of drugs on the body; (3) Bacteria are killed directly in a short time. By adding components with photothermal conversion capabilities to electrospun fibers, electrospun fibers can be given photothermal antibacterial properties. Summary of the invention
[0005] In order to solve the problems that existing wound dressings have poor anti-infection ability, drugs in drug-loaded wound dressings may cause bacterial resistance and drugs may irritate the skin, the present invention provides a nanofiber wound dressing with photothermal and chemical synergistic antibacterial effects and a preparation method thereof.
[0006] The present invention is achieved by the following technical scheme: a nanofiber wound dressing with photothermal and chemical synergistic antibacterial effects, using a PVA / CS solution composed of polyvinyl alcohol PVA and chitosan CS as an electrospinning matrix, adding graphene oxide GO nanoparticles GO-BPEI modified by branched polyethyleneimine BPEI as a photothermal antibacterial component, adding lanthanum chloride as a chemical antibacterial component, preparing an electrospinning solution, and electrospinning the electrospinning solution to obtain a PVA / CS / GO-BPEI / La nanofiber wound dressing.
[0007] The present invention provides a method for preparing the nanofiber wound dressing having photothermal and chemical synergistic antibacterial effects, comprising the following steps: (1) BPEI modified GO to obtain GO-BPEI; (2) PVA / CS solution, GO-BPEI suspension and LaCl3 were mixed to prepare electrospinning solution; (3) electrospinning the electrospinning solution obtained in step (2); (4) The spun nanofibers are vacuum dried, cross-linked with glutaraldehyde vapor, and vacuum dried again.
[0008] The specific preparation method of step (1) GO-BPEI is as follows: dilute 10 mL of GO suspension with a concentration of 2 mg / mL to 1 mg / mL, and ultrasonically disperse for 2 hours; add 1-ethyl-(3-dimethylaminopropyl)carbodiimide EDC solution, N-hydroxysuccinimide NHS solution and branched polyethyleneimine BPEI suspension in sequence under ultrasound, and continue to ultrasonicate for 3 hours until the solution turns dark black; then fully stir the mixture solution for 24 hours, centrifuge at 10000 rpm / min for 20 minutes, collect the precipitate and wash it twice with RO water, and dry it in an oven at 50°C to obtain GO-BPEI, and ultrasonically treat GO-BPEI in RO water to obtain a GO-BPEI aqueous dispersion with a concentration of 2 mg / mL; Among them: EDC solution is 87 mg EDC dissolved in 6 mL RO water; NHS solution is 107 mg NHS dissolved in 4 mL RO water; BPEI suspension is 200 mg BPEI dispersed in 10 mL RO water and the pH is adjusted to 7.6-7.7.
[0009] The preparation method of the PVA / CS solution in step (2) is as follows: 24 g of a 16% PVA solution is mixed with 8 g of a 4% CS solution, the mixture is stirred magnetically for 1 hour, and allowed to stand for 2 hours to remove bubbles; Among them: the PVA solution with a mass concentration of 16% is 8g PVA dissolved in 42mL water; the CS solution with a mass concentration of 4% is 320mg glacial acetic acid dissolved in 7.68mL RO water, and then 0.336g chitosan is added; The preparation method of the electrospinning solution in step (2) is as follows: 5 g of PVA / CS solution is mixed with 5 mL of GO-BPEI suspension with a concentration of 2 mg / mL, and 1.25×10 -4 mol LaCl3, with magnetic stirring overnight.
[0010] The spinning conditions of electrospinning in step (3) are: pushing speed 0.8 mL / h, voltage 20KV, receiving distance 20 cm, motion swing 20 mm, moving speed 10 mm / s; temperature 25-35°C, humidity 20%-30%; the electrospinning method is: load the electrospinning liquid into a 10 mL syringe and electrospin for 10 h.
[0011] In step (4), the glutaraldehyde concentration during glutaraldehyde vapor cross-linking is 10%, and the cross-linking time is 3 h.
[0012] The electrospun fiber film prepared by the present invention is used as a wound dressing by adding GO-BPEI and LaCl3 to a PVA / CS solution and preparing it by an electrospinning method. PVA is used as a spinning aid to enable the solution to be electrospun, and CS provides certain antibacterial properties and improves mechanical properties. GO-BPEI has a photothermal effect and can achieve the purpose of photothermal antibacterial, and the La element in LaCl3 can achieve the purpose of chemical antibacterial. The film used as a wound dressing has excellent antibacterial properties, and at the same time, it has good mechanical properties, air permeability, water absorption, and biocompatibility. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 Characterization of GO and GO-BPEI. In the figure: (a) is the infrared spectrum, (b) is the ultraviolet spectrum, (c) is the particle size distribution, and (d) is the charging condition; Figure 2 The electron microscope images of five nanofiber membranes, fiber diameter distribution and elemental composition of one membrane, PVA / CS / GO-BPEI / La; Figure 3 are the infrared spectra of five nanofiber membranes; Figure 4 The swelling ratio and water vapor permeability of five nanofiber membranes are shown in Figure 1. (a) is the curve of swelling ratio changing with time, (b) is the maximum swelling ratio, and (c) is the water vapor permeability. Figure 5 Mechanical properties of five nanofiber membranes: (a) is the stress-strain curve, (b) is the maximum stress and elongation at break, and (c) is the Young's modulus; Figure 6 In vitro photothermal performance of five nanofiber membranes; Figure 7 The in vitro antibacterial properties of five nanofiber membranes are shown in the figure: (a) is the antibacterial effect of the incubation antibacterial method on Escherichia coli (EC) and Staphylococcus aureus (SA) detected by the plate coating method; (b) is the antibacterial effect of the photothermal antibacterial method on EC detected by the plate coating method and the bacterial morphology observed by scanning electron microscopy; (c) is the antibacterial effect of the photothermal antibacterial method on SA detected by the plate coating method and the bacterial morphology observed by scanning electron microscopy; (d) is the statistical result of the antibacterial rate; Figure 8 In vitro cytotoxicity results of five nanofiber membranes; Fig. 9 The effects of five nanofiber membranes on cell migration. DETAILED DESCRIPTION
[0014] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution will be described below in combination with the embodiments of the present invention and the comparative examples. The described embodiments are part of the embodiments of the present invention, not all of them; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0015] The experimental methods in the following examples are all conventional methods unless otherwise specified. The instruments and equipment used in the following examples are all conventional laboratory instruments and equipment unless otherwise specified; the experimental materials used in the following examples are all purchased from conventional biochemical reagent stores unless otherwise specified.
[0016] The materials and equipment used in the following examples and comparative examples are as follows: Materials: Chitosan (molecular weight 350,000, degree of deacetylation 85%), Shanghai Yuanye Biotechnology Co., Ltd.; polyvinyl alcohol (molecular weight 145,000), Shanghai Aladdin Biochemical Technology Co., Ltd.; glacial acetic acid, Tianjin Fengchuan Chemical Reagent Technology Co., Ltd.; graphene oxide, Qitaihe Baotailong Graphene New Materials Co., Ltd.; EDC, Shanghai Shanghai McLean Biochemical Technology Co., Ltd.; NHS, Shanghai Aladdin Biochemical Technology Co., Ltd.; BPEI, Shanghai McLean Biochemical Technology Co., Ltd.; anhydrous lanthanum chloride, Shanghai McLean Biochemical Technology Co., Ltd.; glutaraldehyde (50%), Tianjin Damao Chemical Reagent Factory.
[0017] Equipment: Analytical balance (BS210s), Beijing Sartorius Balance Co., Ltd.; Constant temperature water bath (XMTB), Beijing Changfeng Instrument Co., Ltd.; High voltage electrospinning machine, Tianjin Yunfan Technology Co., Ltd., Tianjin; Ultrasonic cleaning machine (SB-5200DTD), Ningbo Xinzhi Biotechnology Co., Ltd.; Vacuum drying oven (DZF-6020), Shanghai Boxun Industrial Co., Ltd. Medical Equipment Factory; Magnetic stirrer (MHS4Pro), Qun'an Scientific Instrument (Zhejiang) Co., Ltd.
[0018] Example: Preparation of PVA / CS / GO-BPEI / La nanofiber membrane, prepared by the following steps: 1. Preparation of GO-BPEI: Dilute 10 mL of GO suspension with a concentration of 2 mg / mL to 1 mg / mL, and disperse it by ultrasound for 2 hours; add 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) solution (87 mg EDC dissolved in 6 mL RO water), N-hydroxysuccinimide (NHS) solution (107 mg NHS dissolved in 4 mL RO water) and branched polyethyleneimine (BPEI) solution (200 mg dispersed in 10 mL RO water and adjusted to pH 7.6-7.7) in sequence under ultrasound. Continue ultrasound for 3 hours until the solution turns dark black. Then, stir the mixture solution for 24 hours, centrifuge at 10000 rpm / min for 20 minutes, collect the precipitate, wash it with RO water twice, and dry it in an oven at 50°C to obtain polyethyleneimine-grafted graphene oxide (GO-BPEI). Ultrasonicate GO-BPEI in RO water to obtain a GO-BPEI aqueous dispersion with a concentration of 2 mg / mL.
[0019] 2. Preparation of spinning solution: Preparation of PVA / CS electrospinning liquid matrix: 8 g PVA was dissolved in 42 mL water to prepare a PVA solution with a mass concentration of 16%.
[0020] 320 mg of glacial acetic acid was dissolved in 7.68 mL of RO water, and 0.336 g of chitosan was added to obtain a CS solution with a mass concentration of 4%. 24 g of a PVA solution with a mass concentration of 16% was mixed with 8 g of a CS solution with a mass concentration of 4% to obtain two polymer solutions, which were mixed under magnetic stirring for 1 h and allowed to stand for 2 h to remove bubbles.
[0021] Preparation of PVA / CS / GO-BPEI / La electrospinning solution: 5 g of PVA / CS solution was mixed with 5 mL of 2 mg / mL GO-BPEI solution, and 1.25×10 -4 mol LaCl3, with magnetic stirring overnight.
[0022] 3. Preparation of PVA / CS / GO-BPEI / La nanofiber membrane Electrospinning: The electrospinning solution was loaded into a 10 mL syringe and electrospun for 10 h. The electrospinning parameters were: feed rate 0.8 mL / h, voltage 20 KV, receiving distance 20 cm, motion swing 20 mm, moving speed 10 mm / s. The temperature was 25-35 °C and the humidity was 20%-30%.
[0023] Cross-linking of electrospun membranes: The electrospun membranes were cross-linked with 10 mL of 10% glutaraldehyde vapor for 3 h and then dried in a vacuum oven for 24 h.
[0024] Comparative Example 1: Preparation of PVA nanofiber membrane, prepared by the following steps: 1. Prepare spinning solution: Take 6 g of 16% PVA solution, add 2 mL of water and mix well to prepare a PVA solution with a mass concentration of 12%. Take 5 g of 12% PVA solution, add 5 mL of water, stir magnetically overnight to prepare a 6% PVA spinning solution.
[0025] 2. Preparation of PVA nanofiber membrane: The method is the same as that of the third step of the preparation of PVA / CS / GO-BPEI / La nanofiber membrane in Example 1, except that the PVA / CS / GO-BPEI / La spinning solution is replaced by PVA spinning solution.
[0026] Comparative Example 2: Preparation of PVA / CS nanofiber membrane, prepared by the following steps: 1. Preparation of spinning solution: 5 g of the PVA / CS electrospinning solution matrix prepared in the example was taken, mixed with 5 mL of water, and stirred magnetically overnight to obtain a PVA / CS spinning solution.
[0027] 2. Preparation of PVA / CS nanofiber membrane: The method is the same as that of the third step of the preparation of PVA / CS / GO-BPEI / La nanofiber membrane in Example 1, except that the PVA / CS / GO-BPEI / La spinning solution is replaced by PVA / CS spinning solution.
[0028] Comparative Example 3: Preparation of PVA / CS / GO nanofiber membrane, prepared by the following steps: 1. Preparation of spinning solution: Take 5 g of the PVA / CS electrospinning solution matrix prepared in the example, mix it with 5 mL of GO suspension with a concentration of 2 mg / mL, and stir it magnetically overnight to obtain PVA / CS / GO spinning solution.
[0029] 2. Preparation of PVA / CS / GO nanofiber membrane: The method is the same as that of the third step of the preparation of PVA / CS / GO-BPEI / La nanofiber membrane in Example 1, except that the PVA / CS / GO-BPEI / La spinning solution is replaced by PVA / CS / GO spinning solution.
[0030] Comparative Example 4: Preparation of PVA / CS / GO-BPEI nanofiber membrane, prepared by the following steps: 1. Preparation of spinning solution: Take 5 g of the PVA / CS electrospinning solution matrix prepared in the example and mix it with 5 mL of GO-BPEI suspension with a concentration of 2 mg / mL. The preparation method of GO-BPEI solution is the same as that in the example. Stir magnetically overnight to obtain PVA / CS / GO-BPEI spinning solution.
[0031] 2. Preparation of PVA / CS / GO-BPEI nanofiber membrane: The method is the same as that of the third step of the preparation of PVA / CS / GO-BPEI / La nanofiber membrane in Example 1, except that the PVA / CS / GO-BPEI / La spinning solution is replaced by PVA / CS / GO-BPEI spinning solution.
[0032] From the difference between the embodiments and the comparative examples, the spinning solution of comparative example 1 is the spinning solution of the embodiment except that CS, GO-BPEI and LaCl3 are removed; the spinning solution of comparative example 2 is the spinning solution of the embodiment except that LaCl3 and GO-BPEI are removed; the spinning solution of comparative example 3 is the spinning solution of the embodiment except that LaCl3 is removed, and GO-BPEI is replaced by GO; the spinning solution of comparative example 4 is the spinning solution of the embodiment except that LaCl3 is removed.
[0033] In order to verify the successful preparation of the nanofiber film and prove that the nanofiber film of the embodiment has the best comprehensive performance compared with the other four nanofiber films of the comparative example, the following verification experiments were conducted: Experimental Example 1: This experimental example detected the infrared and ultraviolet spectra of GO and GO-BPEI, analyzed their chemical bond types, proved the successful synthesis of GO-BPEI, and detected the particle size distribution and charge of the two particles in the solution.
[0034] Figure 1(a) shows the infrared spectra of GO and GO-BPEI. GO has a wavelength of 1720 cm -1 The absorption peak that appears belongs to the stretching vibration peak of the carboxyl C=O; at 1630 cm -1 The absorption peak that appears is the stretching vibration peak of C=C in the aromatic ring. -1 The carboxyl band at 1050 cm -1 The disappearance of the alkoxy groups at 1675 cm-1 in GO-BPEI nanoparticles proves that the chemical conjugation of GO is achieved. -1 (-CONH amide band I), 1620 cm -1 (-NH amide band II) and 1456 cm -1The appearance of three new characteristic peaks (CN stretching vibration) confirmed that BPEI had been covalently attached to the surface of GO.
[0035] As shown in Figure 1(b), the UV spectra of GO and GO-BPEI show that GO has absorption peaks at 230 nm and 305 nm, which are caused by the π→π transition of the C=C bond on the aromatic ring and the n→π transition of the C=O bond in the carboxyl group, respectively; while the characteristic peak of GO-BPEI is red-shifted from 230 nm to 264 nm, indicating that the electronic conjugation force between graphene layers has been restored and GO has been reduced to graphene.
[0036] From the particle size distribution diagram in Figure 1(c), it can be seen that the particle size of GO is concentrated in the range of 225-912 nm, while the particle size of GO-BPEI is more concentrated than GO, ranging from 390-1380 nm. The overall average particle size of GO is 989.6 nm, and the average particle size of GO-BPEI nanoparticles is 520.1 nm. Therefore, in the process of grafting GO with BPEI, due to the grafting effect of the carboxyl groups on the surface of GO and the amino groups contained in BPEI, the GO is closely combined, which greatly reduces the size of GO, thereby making the size distribution of GO-BPEI nanoparticles more concentrated.
[0037] As can be seen from Figure 1(d), the edge of GO contains a large number of negatively charged carboxyl groups, which are negatively charged in aqueous solution, and the surface of BPEI contains a large number of amino groups, which are positively charged in aqueous solution. Therefore, by adjusting the ratio of negatively charged carboxylated GO and positively charged BPEI, a GO-BPEI nanoparticle solution with a positive surface charge can be prepared.
[0038] Experimental Example 2: The microstructures of five nanofiber membranes and the elemental composition of the PVA / CS / GO-BPEI / La membrane were detected by scanning electron microscopy.
[0039] The scanning electron microscopy of the electrospun fibers is shown in Figure 2(a). The results show that the electrospun membrane has a uniform nanofiber structure with almost no beads. The membrane has a connected porous structure with uniform membrane thickness. At the same time, graphene oxide sheets can be observed, indicating that the electrospun dressing was successfully prepared. The average diameter of the electrospun nanofibers in each group is approximately between 150-250nm, which is close to the diameter of collagen fibers in the extracellular matrix and can simulate the extracellular matrix.
[0040] As shown in Figure 2(b), the diameter of PVA is 254.76.76±46.95 nm, and the diameter of PVA / CS is 185.29±27.65 nm, indicating that the addition of a small amount of CS can significantly reduce the fiber diameter. The diameter of PVA / CS / GO is 237.92±37.96 nm, and the addition of GO increases the fiber diameter. The diameter of PVA / CS / GO-BPEI is 200.67±40.42 nm, indicating that the addition of GO-BPEI reduces the fiber diameter. The diameter of PVA / CS / GO-BPEI / La is 196.90±38.00 nm, and the addition of La has little effect on the diameter of electrospun nanofibers.
[0041] The elemental composition of the nanofiber membrane is shown in the figure (detected by energy spectrum area analysis). The red, green, and blue dots in Figure 2(c) come from the elements C, O, and N, respectively, and the purple dots come from the element La. The presence of the La element indicates that LaCl3 is successfully loaded onto the film through the electrospinning process. The energy spectrum shows that the C, O, N, and La elements are evenly distributed on the surface of the film, indicating that LaCl3 is well dispersed in the nanofiber film.
[0042] Experimental Example 3: The infrared spectra of five nanofiber membranes were detected.
[0043] Figure 3 FTIR spectra of five nanofiber films: PVA, PVA / CS, PVA / CS / GO, PVA / CS / GO-BPEI, and PVA / CS / GO-BPEI / La. The film with CS added has a wavelength of 3328 cm -1 There is a broad absorption peak at 2920cm, which corresponds to the triplet peak superposition of the hydroxyl group (OH) associated with the primary amine molecule, the free OH and the stretching vibration of NH in CS, which fully indicates that intermolecular hydrogen bonds are formed between CS molecules and PVA to achieve molecular association. Wave number 2920cm -1 The peak at 1724 cm corresponds to the symmetric stretching vibration of CH2, which is a characteristic peak of polysaccharides. -1 The peak corresponding to the C=O stretching vibration peak, 1645 cm -1 The peak corresponds to the C=C stretching vibration peak, 1256cm -1 The absorption peaks are the C=O stretching vibration peaks of the epoxy group, especially the antisymmetric stretching vibration and symmetric stretching vibration. The FTIR spectra of PVA / CS, PVA / CS / GO, PVA / CS / GO-BPEI and PVA / CS / GO-BPEI / La nanofilms do not change significantly.
[0044] Experimental Example 4: The swelling ratio and water vapor permeability of five nanofiber membranes were tested.
[0045] Figure 4 (a) After the samples were immersed in PBS, the PBS absorption rate increased significantly with time, and the swelling equilibrium was reached after immersion for 2-3 minutes. Figure 4 (b) shows that the absorption rates of the five groups of membranes are all between 400% and 500%, with no significant difference, indicating that the wound dressing has a large water absorption capacity, which is conducive to absorbing excess wound exudate and balancing wound moisture. 2 •24h to accelerate wound healing. Figure 4 (c) WVTR experimental results show that the WVTR of the open bottle without nanofiber membrane cover is 9169.88±819.62 g / m 2 •24h. After covering with film, the transmittance is close to 9000g / m 2 •24h, covered with PVA / CS / GO-BPEI / La film: 3832.45±197.95g / m 2 •24 h. Therefore, it can be considered that the prepared electrospun nanofibers can control the water vapor transmission rate, maintain appropriate environmental humidity, and meet the standard of WVTR in wound dressings.
[0046] Experimental Example 5: This test example examined the mechanical properties of five nanofiber films.
[0047] Figure 5 The mechanical properties of different electrospun films are shown. The pure PVA electrospun film has good ductility. After adding components to PVA, the elongation at break is significantly reduced, and the mechanical properties increase to varying degrees. When CS is added to PVA, the elastic modulus and tensile strength of these nanofibers are improved, but the elasticity and fracture strain percentage are lost. Compared with unmodified GO, the fiber membrane with added GO-BPEI has stronger mechanical properties, which may be because GO-BPEI is more evenly distributed in the fiber and has more connections with the fiber. The addition of LaCl3 did not significantly change the mechanical properties of the membrane, which may be because the small content did not have a significant effect on the structure.
[0048] Experimental Example 6: This test example detected the in vitro photothermal conversion performance of five nanofiber membranes.
[0049] The power used is 2 W / cm 2The film was irradiated with an 808 nm near-infrared laser. Figure 6 shows the change of the film temperature over time. The infrared heating performance of the PVA / CS / GO film is relatively weak, rising to 61°C in 5 min. The temperature of the PVA / CS / GO-BPEI and PVA / CS / GO-BPEI / La films rose to 70°C, and the photothermal performance was improved. It can be seen that the modification of GO to GO-BPEI significantly improved the photothermal performance.
[0050] Experimental Example 7: This test example tested the antibacterial properties of five nanofiber membranes. The antibacterial test was conducted in two ways: incubation antibacterial and light antibacterial. Incubation antibacterial was to immerse the nanofiber membrane in Escherichia coli (EC) and Staphylococcus aureus (SA) bacterial suspensions, and photothermal antibacterial was to irradiate the nanofiber membrane with near-infrared light during immersion.
[0051] Figure 7 (a) shows the antibacterial effect of the film incubation method. CS, GO, and GO-BPEI all have a certain antibacterial effect. 3+ After that, the inhibition rate of the two bacteria can reach more than 90%.
[0052] Figure 7 (b) and (c) are the antibacterial effects of photothermal inhibition. From the number of colonies, we can see that compared with incubation inhibition, the addition of GO and GO-BPEI, the photothermal conversion of the film brings high temperature, and the antibacterial effect is further improved. The inhibition rate of PVA / CS / GO-BPEI / La film on the two bacteria is more than 97%. At the same time, it can be seen under SEM that temperature destroys the morphology of bacteria to varying degrees. 3+ Under the combined effect, the bacterial morphology was significantly destroyed.
[0053] Figure 7 (d) is the statistical result of the antibacterial rate, and the other four films are compared with the PVA film with almost no antibacterial performance. Since the PVA / CS / GO-BPEI / La film has dual photothermal / chemical antibacterial properties, it has obvious advantages over other groups.
[0054] Experimental Example 8: In this test example, CCK8 was used to detect the in vitro cytotoxicity of five nanofiber membranes.
[0055] Figure 8 shows the results of detecting the cell viability of fibroblasts (HSFs) on days 1, 3, and 5 using the CCK8 method. The absorbance of the non-electrospun membrane and the five electrospun membranes was compared, and there was no statistically significant difference between day 1 and day 3, indicating that the addition of the electrospun membrane had no substantial toxicity to the cells, and the cell viability was higher than 90%. 5 days after inoculation, the cell viability of the experimental group was lower than that of the control group, but there was no significant difference. All cell viability values could reach 90% of the control group, indicating that the amount of La added to PVA / CS / GO-BPEI / La was not enough to cause significant cytotoxicity of the electrospun membrane.
[0056] Experimental Example 9: This test example used a scratch test to detect the effects of five nanofiber membranes on cell migration rate.
[0057] After scratching, light microscopic images of HSFs migration were collected at 12h, 24h, and 48h (e.g. Fig. 9 (a) ) and imageJ was used for statistical analysis to measure the healing area and evaluate the healing rate of HSFs. Fig. 9 As shown in (b), the healing rate of HSFs12h in the two groups of extracts was about 20%, while the healing rate could reach about 80% after 24h, close to complete healing. It was also found that the migration was relatively fast in the experimental group at 24h. The results showed that there was no significant difference between the experimental group and the control group, and the addition of electrospinning film had no significant effect on cell migration and no significant negative effect on wound healing.
[0058] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, a person skilled in the art can still modify the technical solutions described in the above embodiments, or make equivalent replacements for some or all of the technical features therein.
Claims
1. A nanofiber wound dressing with photothermal and chemical synergistic antibacterial effects, characterized in that: A PVA / CS solution composed of polyvinyl alcohol (PVA) and chitosan (CS) was used as the electrospinning matrix, graphene oxide (GO) nanoparticles (GO-BPEI) modified with branched polyethyleneimine (BPEI) were added as the photothermal antibacterial component, and lanthanum chloride was added as the chemical antibacterial component to prepare an electrospinning solution. The electrospinning solution was electrospun to obtain PVA / CS / GO-BPEI / La nanofiber wound dressing.
2. The nanofiber wound dressing with photothermal and chemical synergistic antibacterial effect according to claim 1, characterized in that: PVA Mw = 145,000, CS deacetylation degree 85%, Mw = 350,000.
3. The nanofiber wound dressing with photothermal and chemical synergistic antibacterial effect according to claim 1, characterized in that: The mass of the electrospinning solution was used as the calculation basis. In the PVA / CS / GO-BPEI / La electrospinning solution, the mass ratio of the PVA / CS electrospinning matrix to the volume ratio of the GO-BPEI suspension was 1 g:1 mL, the mass ratio of PVA to CS in the PVA / CS electrospinning matrix was 12:1, the concentration of the GO-BPEI suspension was 2 mg / mL, and the amount of LaCl3 added to the PVA / CS / GO-BPEI / La electrospinning solution was: 1.25×10 -4 mol LaCl3.
4. The nanofiber wound dressing with photothermal and chemical synergistic antibacterial effect according to claim 1, characterized in that: The nanofiber diameter of the PVA / CS / GO-BPEI / La nanofiber wound dressing is 120-300 nm.
5. A method for preparing the nanofiber wound dressing having photothermal and chemical synergistic antibacterial effects according to any one of claims 1 to 4, characterized in that: The steps include: (1) Modification of GO with BPEI to obtain GO-BPEI; (2) PVA / CS solution, GO-BPEI suspension and LaCl3 were mixed to prepare electrospinning solution; (3) electrospinning the electrospinning solution obtained in step (2); (4) The spun nanofibers are vacuum dried, cross-linked with glutaraldehyde vapor, and vacuum dried again.
6. The preparation method according to claim 5, characterized in that: The specific preparation method of step (1) GO-BPEI is as follows: dilute 10 mL of GO suspension with a concentration of 2 mg / mL to 1 mg / mL, and disperse it ultrasonically for 2 hours; add 1-ethyl-(3-dimethylaminopropyl)carbodiimide EDC solution, N-hydroxysuccinimide NHS solution and branched polyethyleneimine BPEI suspension in sequence under ultrasound, and continue to ultrasonicate for 3 hours until the solution turns dark black; then fully stir the mixture solution for 24 hours, centrifuge at 10000 rpm / min for 20 minutes, collect the precipitate and wash it twice with RO water, and dry it in an oven at 50°C to obtain GO-BPEI, and ultrasonically treat GO-BPEI in RO water to obtain a GO-BPEI aqueous dispersion with a concentration of 2 mg / mL; Among them: EDC solution is 87 mg EDC dissolved in 6 mL RO water; NHS solution is 107 mg NHS dissolved in 4 mL RO water; BPEI suspension is 200 mg BPEI dispersed in 10 mL RO water and the pH is adjusted to 7.6-7.
7.
7. The preparation method according to claim 5, characterized in that: The preparation method of the PVA / CS solution in step (2) is as follows: 24 g of a 16% PVA solution is mixed with 8 g of a 4% CS solution, the mixture is stirred magnetically for 1 hour, and allowed to stand for 2 hours to remove bubbles; Among them: the PVA solution with a mass concentration of 16% is 8g PVA dissolved in 42mL water; the CS solution with a mass concentration of 4% is 320mg glacial acetic acid dissolved in 7.68mL RO water, and then 0.336g chitosan is added; The preparation method of the electrospinning solution in step (2) is as follows: 5 g of PVA / CS solution is mixed with 5 mL of 2 mg / mL GO-BPEI suspension, and 1.25×10 -4 mol LaCl3, with magnetic stirring overnight.
8. The preparation method according to claim 5, characterized in that: The spinning conditions of electrospinning in step (3) are: pushing speed 0.8 mL / h, voltage 20KV, receiving distance 20 cm, motion swing 20 mm, moving speed 10 mm / s; temperature 25-35°C, humidity 20%-30%; the electrospinning method is: load the electrospinning liquid into a 10 mL syringe and electrospin for 10 h.
9. The preparation method according to claim 5, characterized in that: In step (4), the glutaraldehyde concentration during glutaraldehyde vapor cross-linking is 10%, the cross-linking time is 3 h, and the drying time is 24 h.
Citation Information
Cited By
Method for enhancing photo-thermal water evaporation capacity of seaweed non-woven fabric
CN119900170A
Programmable medicine sustained-release nanofiber medical dressing with spider thread structure and preparation method thereof
CN122208808A
Antibacterial polymer composition and method for producing an antibacterial polymer composition
PL249707B1
Antibacterial polymer composition and method for producing an antibacterial polymer composition
PL451975A1
